An investigation of determinants of green consumption behavior: An extended theory of planned behavior - Xiaoyu Zhao; Lidong Fan; Yuan Xu (Innovation and Green Development)
Drawing upon the Theory of Planned Behavior, this research endeavors to delve into the multifarious determinants of green consumption behavior. It extends the traditional Theory of Planned Behavior framework by incorporating information intervention and social trust factors, constructing a comprehensive research model of green consumption behavior. Utilizing a robustly designed questionnaire, this study analyzed data from 354 collected samples using a quantitative research method. The findings revealed that: (1) green consumption attitude and perceived behavioral control significantly influenced green consumption intention, with perceived behavioral control exerting the strongest effect (P ​< ​0.001); (2) green consumption intention, location information, and social trust were significant predictors of green consumption behavior, with the intention being the most influential (P ​< ​0.001); (3) however, subjective norms, green advertising, and ecological labels did not significantly impact green consumption behavior (P ​> ​0.05). Based on these results, the study provides policy recommendations and marketing strategies to facilitate the promotion of green consumption practices.